The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.1177/1045159519854547
|View full text |Cite
|
Sign up to set email alerts
|

Workforce Development Through Online Experiential Learning for STEM Education

Abstract: The U.S. workforce is increasingly comprised of older adults, women, and minorities who lack basic skills and are unable to acquire these skills through traditional educational and training programs. New approaches are needed to provide effective training to the adult learner and flexible support for nontraditional students who must balance work-life demands with limited educational opportunities. Contextualized teaching and learning (CTL) is a form of experiential learning that blends both basic skills and oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…Female participants achieved higher rates of credentialing compared to all other demographic groups in both the CTL and non-CTL groups, despite more than two-thirds of female participants being enrolled only part-time. The research shows there are few numbers of female students in the manufacturing and construction programs [12,29]. However, knowing the results of female students in the online contextualized program is very promising, and augments what the literature suggested in terms of the underrepresentation of women in STEM and the enormous potential for them to enter into these fields, which is also consistent with what other studies revealed in the literature [30].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Female participants achieved higher rates of credentialing compared to all other demographic groups in both the CTL and non-CTL groups, despite more than two-thirds of female participants being enrolled only part-time. The research shows there are few numbers of female students in the manufacturing and construction programs [12,29]. However, knowing the results of female students in the online contextualized program is very promising, and augments what the literature suggested in terms of the underrepresentation of women in STEM and the enormous potential for them to enter into these fields, which is also consistent with what other studies revealed in the literature [30].…”
Section: Discussionsupporting
confidence: 81%
“…The community colleges of this part of the U.S.A. [12] serve a highly diverse population, which is comprised of both traditional and non-traditional students. Non-traditional students include large numbers of underrepresented people, such as women, minorities, and veterans who are STEM majors in community colleges.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, there is currently no single opinion on the essence of STEM technique. Some researchers associate it with contextual teaching and learning as experiential learning and mixing basic skills with real-life training [26]. The STEM range of problems cannot be understood in a mono-disciplinary context as it requires studying the impact of the methodology immediately on a group of disciplines.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, a number of studies indicate that e-learning is less effective for groups of students at increased risk of underperforming or expelling from the educational process and their chances of getting a degree are reduced [24,25]. Such risk groups include women, "people of colour" and Afro-American students, representatives of non-traditional social groups, students from low-income families, and those who are the first university-student in a family [12,25,26]. Moreover, according to the available statistical data, the representatives of these risk groups make up from half to the vast majority of students from a number of institutions in the USA, some European countries, and many Asian countries [12].…”
Section: Introductionmentioning
confidence: 99%
“…• Identify approaches to online science instruction that incorporate hands-on or experiential learning (Beier et al, 2019;Mohammadi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%